MENGENAL PENDIDIKAN MULTIKULTURAL BAGI ANAK BERKEBUTUHAN KHUSUS DENGAN MODEL INKLUSI DALAM PENDIDIKAN ISLAM - Sulthon, Sulthon (ADDIN, 2013)
MULTICULTURAL EDUCATION FOR CHILDREN WITH SPECIAL NEEDS USING INCLUSION MODEL IN ISLAMIC EDUCATION. Education is a right of all citizens regardless of social status, race, ethnicity, tribe, nation, including children with disabilities. Thus, these children also have the same rights as children in general on the occasion of viable, appropriate and dignified education. In fact children with disabilities cannot take education freely because not all of the existing school could serve them because of the classical reasons. The Schoolproviding education for these children is still appreciative and ironic that needs a struggle to become democratic education. Ideally with integrated education, children with disabilities can be served in schools wherever they want, including choosing a school in Islamic school. This would be an option for them since both parents and students with disabilities require touches with regard to awareness, faith, and sincerity. The religious approach became a highly influential part in all conditions and situations faced by humanity, because in fact the man will always be united with his Lord through the development of spirituality.